Dietary Carbohydrate Intake and New-Onset Hypertension: A Nationwide Cohort Study in China. Issue 2 (8th February 2021) - Li, Qinqin; Liu, Chengzhang; Zhang, Shaojie; Li, Rui; Zhang, Yuanyuan; He, Panpan; Zhang, Zhuxian; Liu, Mengyi; Zhou, Chun; Ye, Ziliang; Wu, Qimeng; Li, Huan; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : The association between carbohydrate intake and the risk of hypertension remains uncertain. We aimed to evaluate the prospective relations of the amount and type of carbohydrate intake with new-onset hypertension. A total of 12 177 adults who were free of hypertension at baseline from the China Health and Nutrition Survey were included. Dietary intake was measured by 3 consecutive 24-hour dietary recalls combined with a household food inventory. The study outcome was new-onset hypertension, defined as systolic blood pressure ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg or diagnosed by physician or under antihypertensive treatment during the follow-up. A total of 4269 subjects developed hypertension during 95 157 person-years of follow-up. Overall, there was a U-shaped association between the percentage energy consumed from total carbohydrate (mean, 56.7%; SD, 10.7) and new-onset hypertension ( P for nonlinearity <0.001), with the lowest risk observed at 50% to 55% carbohydrate intake. The increased risks were mainly found in those with lower intake of high-quality carbohydrate (mean, 6.4%; SD, 5.6) or higher intake of low-quality carbohydrate (mean, 47.0%; SD, 13.0). Moreover, there was an inverse association between the plant-based low-carbohydrate scores for low-quality carbohydrate and new-onset hypertension. However, there was a U-shaped association between the animal-based low-carbohydrate scores for low-quality carbohydrate and new-onset hypertension ( P for nonlinearity <0.001). In summary, both high and low percentages of carbohydrate diets were associated with increased risk of new-onset hypertension, with minimal risk at 50% to 55% carbohydrate intake. Our findings support the intake of high-quality carbohydrate, and the substitution of plant-based products for low-quality carbohydrate for prevention of hypertension.